Factors involved in human papillomavirus (HPV) vaccine hesitancy among women in the South-East Asian Region (SEAR) and Western Pacific Region (WPR): A scoping review - Diviya Santhanes; Che Pui Wong; Yan Ye Yap; Saw Pui San; Nathorn Chaiyakunapruk; Tahir Mehmood Khan (Taylor & Francis Group, 2018)
A scoping review was performed to identify factors that may lead to human papillomavirus (HPV) vaccine hesitancy among women in low- and middle-income countries in South East Asian Region (SEAR) and Western Pacific Region (WPR). A systematic search of English and non-English articles using Pubmed, EMBASE, PsycINFO, Cochrane, MEDLINE, and CINAHL plus was conducted. Only 63 studies conducted in SEAR and WPR were included from inception until December 2016. Results of these studies have shown that poor awareness and knowledge of practices on cervical cancer prevention was evident in both SEAR and WPR. Concerns on safety and efficacy of the vaccine, and costs in getting vaccinated were significant barriers. Most women stated that they needed more information, and strongly welcomed a physician's recommendation in both geographical regions. Women also felt they have a low risk of acquiring HPV infection and cervical cancer. Most women in SEAR and WPR were unable to decide on whether to accept HPV vaccination.